Hemorheological profiles and chronic inflammation markers in transfusion-dependent and non-transfusion- dependent thalassemia - Caprari, Patrizia; Profumo, Elisabetta; Massimi, Sara; Buttari, Brigitta; Riganò, Rachele; Regine, Vincenza; Gabbianelli, Marco; Rossi, Stefania; Risoluti, Roberta; Materazzi, Stefano; Gullifa, Giuseppina; Maffei, Laura; et al. (Frontiers in Molecular Biosciences, 2023)
The rheological properties of blood play an important role in regulating blood flow in micro and macro circulation. In thalassemia syndromes red blood cells exhibit altered hemodynamic properties that facilitate microcirculatory diseases: increased aggregation and reduced deformability, as well as a marked increase in adherence to the vascular endothelial cells. A personalized approach to treating thalassemia patients (transfusions, iron chelation, and splenectomy), has increased patients' life expectancy, however they generally present many complications and several studies have demonstrated the presence of high incidence of thromboembolic events. In this study the hemorheological profiles of thalassemia patients have been characterized to point out new indices of vascular impairment in thalassemia. Plasma viscosity, blood viscosities at low and high shear rates (η1 and η200, respectively), erythrocyte aggregation index (η1/η200), and the erythrocyte viscoelastic profile (elastic modulus G', and viscous modulus G") have been studied in transfusion-dependent and non-transfusion-dependent thalassemia patients. Moreover, the levels of inflammation biomarkers in thalassemia have been evaluated to investigate a relationship between the biomarkers, the disease severity and the rheological parameters. The biomarkers studied are the main components of the immune and endothelial systems or are related to vascular inflammation: cytokines (IL-2, IL-6, IL-10, IL-17A, TNF-alpha), chemokines (IL-8, MIP-1alpha), adipocytokines (leptin and adiponectin), growth factors (VEGF, angiopoietin-1), adhesion molecules (ICAM-1, VCAM-1, E-selectin, L-selectin), and a monocyte/macrophage activation marker (CD163). This study shows that transfusion-dependent thalassemia patients, both major and intermedia, have blood viscosities comparable to those of healthy subjects. Non-transfusion-dependent thalassemia intermedia patients show high blood viscosities at low shear rates (η1), corresponding to the flow conditions of the microcirculation, an increase in erythrocyte aggregation, and high values of the elastic G' and viscous G" modules that reflect a reduced erythrocyte deformability and an increase in blood viscosity. Levels of cytokines, chemokines and adhesion molecules are different in transfusion- and non-transfusion dependent patients and positive correlations between η1 or η1/ η200 and the cytokines IL-6 and IL-10 have been observed. The evaluation of the hemorheological profiles in thalassemia can provide new indicators of vascular impairment and disease severity in thalassemia in order to prevent the onset of thromboembolic events.